A Study on the Inhomogeneous Sedimentation—Diagenesis– Reservoir Formation Mode of Deep Tight Marine Clastic Rock Reservoirs in the Silurian Xiaoheba Formation, Southeast Sichuan - Cheng, Lixue (Frontiers in Earth Science, 2022)
By means of thin section authentication, physical characteristics analysis, scanning electron microscopy (SEM), X-ray diffraction, and vitrinite reflectance analysis, this paper, based on regional geological research achievements, studies the sedimentary facies and diagenesis of the southern and northern Silurian Xiaoheba Formation areas of Southeast Sichuan and their relationships with the physical characteristics of the reservoirs. The results indicate that, in the northern study area, the microfacies are mainly deposited in the underwater distributary main channel of the distal shallow-water delta front; while in the south, the microfacies include an estuary bar, sheet sand, distal bar, and interdistributary bay, which are far away from the main channel. The physical characteristics of sandstone are positively correlated with its particle sizes and thickness. The sand body of the underwater distributary main channel microfacies features high porosity, large crack opening, and good connectivity, followed by the sandstone of the estuary bar microfacies regarding those characteristics. By contrast, the physical characteristics of the sandstone reservoirs corresponding to the microfacies including the distal bar, sheet sand, and interdistributary bay are poor. The Xiaoheba Formation reservoir is located in the late diagenetic stage, with the reservoir space dominated by dissolved pores and micro-cracks; the diagenesis and pore evolution in the south are significantly different from those in the north. The Xiaoheba Formation reservoir in the northern area is far away from the carbonate rock platform of the same period in the south but is close to the center of hydrocarbon generation. Besides, the reservoir was sufficiently reformed by organic acid dissolution in the early-medium diagenetic stage, with only a little carbonate cementation formed in the early stage, while the cementation in the late diagenetic stage was weak. Therefore, the reservoir pores were relatively well preserved. However, the Xiaoheba Formation reservoir in the southern area has a large amount of calcite cement that was formed in the early diagenetic stage and the pores were blocked due to the influence of the carbonate platform. Since the dissolution was weak at the same time, the reservoir in the southern area is tight. Based on the understanding above, this paper established the inhomogeneous sedimentation–diagenesis–reservoir formation mode of the northern and southern areas of the study area.